Personalized neoantigen hydrogel vaccine combined with PD-1 and CTLA-4 double blockade elicits antitumor response in liver metastases by activating intratumoral CD8+CD69+ T cells - Huan Yang; Ming Wu; Yongyi Zeng; Geng Chen; Zhixiong Cai; Xiaolong Liu; Da Zhang; Xiuqing Dong; Shichuan Tang; Ruijing Tang; Kongying Lin; Jun Fu; et al. (Journal for ImmunoTherapy of Cancer)
Background Liver metastasis is highly aggressive and immune tolerant, and lacks effective treatment strategies. This study aimed to develop a neoantigen hydrogel vaccine (NPT-gels) with high clinical feasibility and further investigate its efficacy and antitumor molecular mechanisms in combination with immune checkpoint inhibitors (ICIs) for the treatment of liver metastases.Methods The effects of liver metastasis on survival and intratumor T-cell subpopulation infiltration in patients with advanced tumors were investigated using the Surveillance, Epidemiology, and End Results Program (SEER) database and immunofluorescence staining, respectively. NPT-gels were prepared using hyaluronic acid, screened neoantigen peptides, and dual clinical adjuvants [Poly(I:C) and thymosin α-1]. Then, the efficacy and corresponding antitumor molecular mechanisms of NPT-gels combined with programmed death receptor 1 and cytotoxic T-lymphocyte-associated protein 4 double blockade (PCDB) for the treatment of liver metastases were investigated using various preclinical liver metastasis models.Results Liver metastases are associated with poorer 5-year overall survival, characterized by low infiltration of cytotoxic CD8+ T cells and high infiltration of regulatory T cells (Tregs). NPT-gels overcame the challenges faced by conventional neoantigen peptide vaccines by sustaining a durable, high-intensity immune response with a single injection and significantly improving the infiltration of neoantigen-specific T-cell subpopulations in different mice subcutaneous tumor models. Importantly, NPT-gels further combined with PCDB could enhance neoantigen-specific T-cell infiltration and effectively unlock the immunosuppressive microenvironment of liver metastases, showing superior antitumor efficacy and inducing long-term immune memory in various preclinical liver metastasis models without obvious toxicity. Mechanistically, the combined strategy can inhibit Tregs, induce the production and infiltration of neoantigen-specific CD8+CD69+ T cells to enhance the immune response, and potentially elicit antigen-presenting effects in Naïve B_Ighd+ cells and M1-type macrophages.Conclusions This study demonstrated that NPT-gels combined with PCDB could exert a durable and powerful antitumor immunity by enhancing the recruitment and activation of CD8+CD69+ T cells, which supports the rationale and clinical translation of this combination strategy and provides important evidence for further improving the immunotherapy efficacy of liver metastases in the future.